2017
DOI: 10.1111/pbr.12463
|View full text |Cite
|
Sign up to set email alerts
|

Survey of the Bru1 gene for brown rust resistance in Brazilian local and basic sugarcane germplasm

Abstract: Bru1 is currently the major gene conferring brown rust resistance in sugarcane, and diagnostic markers are available. A survey for the presence of this gene was conducted on 391 genotypes including Brazilian cultivars, clones and basic germplasm. The efficiency of these markers for identifying resistant cultivars and artificially inoculated basic germplasm was also evaluated. The Bru1 frequency among cultivars (73.5%) suggests this gene is the prevalent source of brown rust resistance in Brazilian sugarcane br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…The low prevalence of the Bru1 gene in the EEAOC´s germplasm was previously reported by Racedo et al [12], whereas, Brazilian accessions showed a high frequency of haplotype I, revealing a genetic fixation effect of Bru1 in this germplasm, mainly for breeding genotypes. Similar results were presented by Neuber et al [14] and Barreto et al [39].…”
Section: Plos Onesupporting
confidence: 92%
See 1 more Smart Citation
“…The low prevalence of the Bru1 gene in the EEAOC´s germplasm was previously reported by Racedo et al [12], whereas, Brazilian accessions showed a high frequency of haplotype I, revealing a genetic fixation effect of Bru1 in this germplasm, mainly for breeding genotypes. Similar results were presented by Neuber et al [14] and Barreto et al [39].…”
Section: Plos Onesupporting
confidence: 92%
“…In a previous study where sugarcane accessions of EEAOC´s bank were evaluated under field infection, only 16.3% of resistant genotypes to brown rust harboured the Bru1 gene [12], proposing the existence of other alternative resistant sources, recently confirmed by Chaves et al [13]. Whereas a high frequency of Bru1 (73.5%) among brazilian cultivars suggested this gene is the prevalent source of brown rust resistance in Brazilian sugarcane breeding programmes [14], reinforcing the importance of germplasm exchange between both programs. Regarding orange rust, another major disease impacting sugarcane production worldwide caused by P. kuehnii, a PCR-based resistance gene-derived maker, G1 was developed and it can be effectively utilized in sugarcane breeding programs to facilitate the selection process [15].…”
Section: Introductionmentioning
confidence: 89%
“…Association mapping method was also used based on 119 sugarcane genotypes fingerprinted for 944 SSR alleles, and four sugarcane red rot resistance markers were obtained ( Singh et al, 2016 ). However, to date, Bru1 PCR diagnostic markers for identifying brown rust resistant cultivars remains the only example of marker-assisted selection (MAS) in sugarcane ( Costet et al, 2012 ; Glynn et al, 2013 ; Racedo et al, 2013 ; Li et al, 2016 ; Neuber et al, 2017 ). Thus, studies validating sugarcane DNA markers in breeding program or germplasm identification remain very limited.…”
Section: Introductionmentioning
confidence: 99%
“…Bru1 , detected in the cultivar R570, is a major gene with dominant effect (Daugrois et al, 1996). The presence of Bru1 was evaluated in different sugarcane germplasm around the world (Costet et al, 2012; Glynn et al, 2013; Li et al, 2017; Neuber et al, 2017; Parco et al, 2014, 2017; Racedo et al, 2013). Overall, results showed a high presence of Bru1 in modern resistant cultivars, making the durability of the Bru1 resistance gene vulnerable.…”
Section: Introductionmentioning
confidence: 99%